Preserving the Breath of Javanese Culture in the Era of Globalization: Macapat Singing Training for the Ngesti Laras Art Group, Tulungagung - Teguh, Teguh; Adibah, Ayuk Wahdanfiari; Kalimah, Siti (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
The preservation of local culture is a crucial aspect in safeguarding national identity amidst the currents of globalization. One form of Javanese culture that holds high historical and philosophical value is macapat, a traditional form of singing that conveys moral, ethical, and spiritual teachings. This community service project aims to develop the skills of the younger generation and foster their love for Javanese art and culture through macapat singing training, while also establishing a well-structured and sustainable organization for the Ngesti Laras Art Group in Tulungagung. The method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the macapat training not only enhanced the musical skills of the participants but also raised their awareness of the importance of preserving cultural heritage. Participants experienced significant improvement in understanding and performing macapat songs, supported by the training module provided. Additionally, the formation of an organizational structure consisting of a chairperson, secretary, treasurer, and work divisions provided clear direction and defined roles in managing the group's activities. The recommendation from this initiative is for similar training programs to be conducted continuously, involving more youth and support from educational institutions or local governments, so that local cultural preservation can be carried out more systematically and sustainably. This training serves as a means of regenerating traditional art practitioners and strengthening the cultural identity of the local community. In conclusion, macapat training is an effective strategy for preserving Javanese culture, particularly within local art communities.